“WE ARE GOING TO WATCH A VIDEO...”: LESSONS LEARNT DURING THE ESP CLASSROOM - Andreea BAN; Adrian NĂZNEAN (Revista de Pedagogie, 2022)
The COVID-19 pandemic which forced the transfer of education from the physical to the virtual environment led to the exploitation of various materials and resources for teaching English for specific purposes. The use of videos in online lessons was investigated in a study conducted on four mixed-ability groups of students exposed to various educational videos to varying extents. The videos intended to improve the acquisition of vocabulary for English for specific purposes, namely for engineering and medicine. The students were divided into four groups, two engineering groups, and two medicine ones. All students were in their second undergraduate year and all had two lectures of English per week. One engineering group and one medicine group were exposed to at least two videos per course, whereas the other groups to one or no videos per course. Vocabulary acquisition was assessed using MCQs, word formation, and gap filling exercises, whereas speaking activities were conducted in smaller groups in virtual rooms. Following the 10-week period, not only the students’ vocabulary improved, but also their speaking abilities especially in the groups that used at least two videos per lesson, while the other groups showed only modest improvement of vocabulary acquisition and speaking skills.